Синтез полного и сокращенного наблюдателей двух массовой электромеханической системы - Балюта, Сергей Николаевич; Бурляй, Игорь Юриевич; Копылова, Людмила Александровна; Клименко, Юлия Александровна (My University, 2013)
The method of synthesis of full and reduced observer on the basis of Luenberger observer is presented in the article. Input variables of a mechanical subsystem of speed regulation of the main drive are the determined variables, namely torque setting and load torque. Analytical formulations of a feedback vector of full and reduced observer depending on the position of poles of the observer have been received. Damping properties and dynamics of the observer are set by parameters of time constant of the observer and factor of damping of the observer. Comparison of properties of various condition observers with the help of singular values has shown that when changing the moment of control system loading on variables of a condition with full and reduced observer there is proper drive and loading rotary speed damping per minute. Thus, almost the entire frequency range of drive speed oscillations and load speed is better damped by a system with reduced observer, than by a system with the observer of a full order. The analysis of transitive characteristics on disturbance, depending on the observer used has allowed establishing the fact that setting the torque of a larger scale is a necessary part of disturbance characteristics in system with the observer of a full order. The use of the reduced observer allows more dynamical regulation of deviation at load jump; the fluctuations caused by change of load torque on a shaft are much more effectively damped in a closed looped control system on condition with the reduced observer in comparison with using other regulators. В статье представлен метод синтеза полного и сокращенного наблюдателя на основе наблюдателя Люинбергера. Входными величинами механической подсистемы регулирования скорости главного привода являются детерминированные переменные уставка момента и момент нагрузки. На основе задания положения полюсов характеристического уравнения получены аналитические выражения вектора обратной связи полного и сокращенного наблюдателя.
Keywords: full order observer; reduced observer; luenberger observer; наблюдатель Люинбергера; наблюдатель полного порядка; сокращенный наблюдатель; кафедра електропостачання і енергоменеджменту